2020
DOI: 10.1155/2020/6662634
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Learning Styles and Career Decision-Making Self-Efficacy among Medicine and Dentistry Students of Ardabil University of Medical Sciences

Abstract: Background and Objectives. The career decision-making self-efficacy (CDSE) in medical, pharmacy, and dental students is more important than other disciplines due to professional sensitivity, direct involvement in decision-making for the treatment process, and the significant clinical involvement. It is also expected that learning styles can have a significant impact on the academic success, and the CDSE also affects the quality of clinical care. Therefore, the aim of this study was to examine the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Based on the self-regulated learning theory, we propose that students' learning adaptation in the information-based teaching environment includes five dimensions: learning motivation, information acquisition methods, metacognitive strategies, knowledge acquisition, and knowledge expansion [ 19 ]. Learning motivation refers to the internal motivation that directly promotes students' learning; information acquisition means the ability to obtain learning resources through information technology; metacognitive strategy refers to the strategy of controlling the process of information and monitoring and guiding the cognitive process; knowledge acquisition and knowledge expansion focus on students' ability to understand and apply knowledge at different stages of the learning process [ 20 ]. The questionnaire on students' learning adaptability in the information-based teaching environment (initial version) includes 40 questions, including 8 questions on learning motivation, 6 questions on information acquisition, 8 questions on metacognitive strategies, 12 questions on knowledge acquisition, and 6 questions on knowledge expansion.…”
Section: Results and Analysismentioning
confidence: 99%
“…Based on the self-regulated learning theory, we propose that students' learning adaptation in the information-based teaching environment includes five dimensions: learning motivation, information acquisition methods, metacognitive strategies, knowledge acquisition, and knowledge expansion [ 19 ]. Learning motivation refers to the internal motivation that directly promotes students' learning; information acquisition means the ability to obtain learning resources through information technology; metacognitive strategy refers to the strategy of controlling the process of information and monitoring and guiding the cognitive process; knowledge acquisition and knowledge expansion focus on students' ability to understand and apply knowledge at different stages of the learning process [ 20 ]. The questionnaire on students' learning adaptability in the information-based teaching environment (initial version) includes 40 questions, including 8 questions on learning motivation, 6 questions on information acquisition, 8 questions on metacognitive strategies, 12 questions on knowledge acquisition, and 6 questions on knowledge expansion.…”
Section: Results and Analysismentioning
confidence: 99%
“…Relevant studies have found that in a mixed teaching environment, students' selfefficacy is correlated with academic performance (Warren et al, 2020), and self-efficacy is positively correlated with self-regulated learning strategies (Lee et al, 2020). Career decision-making self-efficacy is also correlated with students' learning styles (Farhang et al, 2020). Akamatsu et al (2019) demonstrated that selfefficacy played a mediating role in the process of metacognitive strategies and self-regulated learning and illustrated the correlation between self-efficacy and learning strategies.…”
Section: The Mediating Role Of Self-efficacy Between Perceived Teache...mentioning
confidence: 98%
“…Although it is true that the cognitive part is very important for the development of the student; but it would have a comprehensive panorama of being developed in values, ethics; in development as a person, who is aware of how to be a collaborative person, who contributes to his society by developing activities that respond to social problems, social pollution and the objectives of sustainable development. Competences are acquired in students according to what has been established in the curricular plan of each university; what comes to do the north of the graduate profile [63], [64]. The skills acquired by the students will depend on the different learning styles that are applied in the class sessions of the different subjects [69], [70].…”
Section: Q2: How Are Teaching Strategies Related To Learning Styles?mentioning
confidence: 99%